Monitoring and enforcement of Code-based legal measures to protect breastfeeding in South Asia: opportunities and bottlenecks - Ching, Constance; Sethi, Vani; Clark, David Lawson; Yeong, Joo Kean; Shats, Katherine; Murira, Zivai; Aminee, Ahmadwali; Rowel, Dhammica; Khan, Golam Mohiuddin; Ahmed, Khadheeja; Dorji, Kinley; Iqbal, Mazhar; et al. (Frontiers in Public Health, 2025)
ObjectiveTo examine the bottlenecks and opportunities associated with Code monitoring and enforcement at the national level in the eight countries of South Asia region (Afghanistan, Bhutan, Bangladesh, India, Maldives, Nepal, Pakistan, and Sri Lanka).DesignData was collected following a workshop-as-research methodology. Deductive content analysis was used to review, categorize, and analyze data. A semi-structured categorization matrix containing three main categories (background, opportunities, and bottlenecks) was developed as a guide for categorizing data on areas relevant to monitoring and enforcement.FindingsOverarching themes in bottlenecks include: (1) There is insufficient monitoring across countries, (2) Monitoring is not well-integrated into relevant enforcement mechanisms, as there is a lack of established system to efficiently ‘feed’ monitoring findings to the designated enforcement agencies, (3) Uncertainty regarding enforcement in the context of digital marketing, (4) Lack of coordination and collaboration regarding enforcement, (5) Inadequate sanctions and penalties, sometimes due to a lack of identified legal structure and adjudication system and functional administrative or enforcement mechanisms. Overarching themes in opportunities include: (1) Product registration or licensing as entry points for monitoring and enforcement, (2) authority provided in legal measures for designated agencies to carry out monitoring and enforcement actions, (3) civil society as government partners in monitoring including developing monitoring tools and strengthening systems to integrate monitoring with enforcement. Inadequately imposed.